ADSORPSI PENGOTOR MINYAK DAUN CENGKEH OLEH LEMPUNG TERAKTIVASI ASAM - P. Suarya (Jurnal Kimia (Journal of Chemistry), 2008)
Preparation, characterization and application of acid activated clays as adsorbents on the purification of clove leavesoil have been conducted. The effects of concentration of acid on the quality of the activated clay and on theadsorption performance of the prepared activated clay were also studied. Characterization of the activated clay wascarried out using gas sorption analyzer and FTIR spectroscopyThe results showed that the spesific surface area of the activated clays increases with increasingconcentration of acid. At the concentration of acid of 0, 0.4, 0.8, 1.2, 1.6, and 2.0 M, the spesific surface areas were48.27; 48.75, 54.31; 65.21; 62.91 and 51.86 m2/g, respectively. From the adsorption test, it was observed that theactivated clay prepared with concentration acid of 1,2 M, showed the best performance. It’s was able to adsorp 284.2mg of impurity and thus purify 40 ml of crude clove leaves oil.